Onnen maille: Romaani - Brand, Max, 1892-1944; Kupiainen, Alpo, 1888-1937 (Salt Lake City, UT : Project Gutenberg, 2022)
"Onnen maille: Romaani" by Max Brand is a novel written in the early 20th century. The story revolves around John Scovil and his daughter Nancy as they navigate life in a remote western setting, where Scovil's optimism about the surroundings contrasts with Nancy's more cynical disposition. The narrative hints at themes of adventure, family dynamics, and the search for happiness. The opening of the book introduces John Scovil, who takes joy in the mountain desert's climate and seems eager to revel in nature's beauty. He interacts with his daughter Nancy, who appears indifferent to his enthusiasm about their surroundings. Scovil's concern for Nancy's well-being is evident as he notes her lack of energy and engagement in the outdoor activities he proposes. As they converse, Scovil's desire to revitalize Nancy's spirit is contrasted by her reluctance, setting up the emotional stakes of their relationship. This initial chapter establishes a foundation for exploring their journey towards understanding and potentially transforming their lives as they venture into the wilderness. (This is an automatically generated summary.)
Release date is 2022-12-04
Timo Ervasti and Tapio Riikonen
Keywords: Western stories